New species of Mycena (Basidiomycota, Agaricales) from California - Perry, Brian A.; Desjardin, Dennis E. (Phytotaxa, 2016)
Two new species of Mycena are described from California: Mycena nivicola, a spring taxon from the High Sierra Nevada and Cascade Ranges is proposed within section Hygrocyboideae, and M. bulliformis from the Coastal Ranges and Sierra Nevada Foothills is proposed in section Rubromarginatae. Both species are fully described, illustrated, and compared with similar and/or closely related taxa.